Aaron Burr and Mary Shelley's Lodore. (2nd January 2022) - Brewer, William D.
ABSTRACT: During Aaron Burr's two sojourns in England, which occurred when Mary Shelley was 10, 11, and 14 years old, the disgraced former American Vice President frequently visited her family. Now best known for slaying Alexander Hamilton in an 11 July 1804 duel, Burr was a fervent admirer of Shelley's mother, Mary Wollstonecraft, and a devoted father to his daughter Theodosia Burr Alston, whom he had educated according to the principles promulgated in A Vindication of the Rights of Woman . Like Burr, the title-character of Shelley's novel Lodore is a mercurial figure who has an extremely close relationship with his daughter, carefully supervises her education, and fights a fatal duel near New York City. Lodore also features another dedicated father, Lord Lodore's friend Francis Derham, who trains his daughter Fanny to be 'independent and self-sufficing.' In this article, I explore the possibility that Shelley's girlhood acquaintance with Burr influenced her depictions of Lodore and of Derham's Wollstonecraftian education of Fanny. If Shelley's portrayals of Lodore and Derham were informed by her acquaintance with Burr, they suggest that she considered Burr's restless ambition, adherence to the violent code duello, and quixotism harmfully misguided but admired his commitment to his daughter and her 'masculine' education.